PRMT5 is essential for B cell development and germinal center dynamics - Ludivine C. Litzler (Nature Portfolio, 2019)
Protective antibody responses depend critically on proper B cell development and differentiation at multiple stages. Here the authors show that a protein arginine methyltransferase, Prmt5 uses multiples pathways to prevent death of immature B cells, yet modulates, in p53-independent manners, the survival and differentiation of mature B cells.